2012
DOI: 10.1001/archfacial.2012.43
|View full text |Cite
|
Sign up to set email alerts
|

A Review of 13 Years of Experience With Endoscopic Forehead-lift

Abstract: Endoscopic forehead-lift enables long-lasting results with highly satisfied patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Unilateral facial nerve paresis (frontal branch) was observed in 5.8% of the patients. Its frequency was 5% 25 and 6% 12 in the 2 previous large series. Undercorrection was a concern in 7.1% of our series.…”
Section: Complicationsmentioning
confidence: 64%
“…Unilateral facial nerve paresis (frontal branch) was observed in 5.8% of the patients. Its frequency was 5% 25 and 6% 12 in the 2 previous large series. Undercorrection was a concern in 7.1% of our series.…”
Section: Complicationsmentioning
confidence: 64%
“…A considerable number of surgeons chose the subperiosteal bone as the dissection plane and used grasp forceps to ablate the corrugators and procerus; then, without handling the frontalis muscle, and they used brow-lifting devices to achieve forehead lift. 2,5,[17][18][19] These techniques were proven to be effective in morphometric evaluation 5,17,18 and PROs. 17 Regarding a surgical technique with soft tissue dissection but without the assistance of brow-lifting devices, Citarella et al reported that such a procedure had good subjective outcomes but lacked morphometric evaluation.…”
Section: Two Innovative Steps In Surgical Proceduresmentioning
confidence: 99%
“…2,5,[17][18][19] These techniques were proven to be effective in morphometric evaluation 5,17,18 and PROs. 17 Regarding a surgical technique with soft tissue dissection but without the assistance of brow-lifting devices, Citarella et al reported that such a procedure had good subjective outcomes but lacked morphometric evaluation. 20 Two innovative operation steps were applied in our surgical procedure: First, we chose the inferior plane of the frontal muscle as the operative surface.…”
Section: Two Innovative Steps In Surgical Proceduresmentioning
confidence: 99%
“…Several techniques exist to treat ptosis of the eyebrows 5,[9][10][11][12][13][14][15][16][17][18] . Some only treat brow ptosis, and other techniques are also used for treating a wide spectrum of facial aging changes.…”
Section: Introductionmentioning
confidence: 99%
“…In 1994 Vasconez et al 22 first described the endoscopic browlift technique, which has been widely studied [10][11][12]14,[23][24][25][26][27][28][29][30][31][32] . This is a popular technique since advantages include less scarring, alopecia and numbness posterior to the scar.…”
Section: Introductionmentioning
confidence: 99%